OBSERVASI JENIS PARASITOID LARVA PENGGULUNG DAUN PISANG Erionata thrax Linnaeus (Lepidoptera: Hesperidae) PADA KETINGGIAN TEMPAT YANG BERBEDA DI KABUPATEN SIGI - Rahmawati, Rahmawati; Pasaru, Flora; Yunus, Mohammad (AGROTEKBIS, 2018)
Banana plant is a plant easily cultivated and is often found to being able to grow and develop well in various agro-ecological conditions. Banana skipper E. Thrax is a destructive pest which make leaves to roll by cutting and feeding a section of a leaf, starting from the edge of the leaf running parallel to the main leaf bone and glued with whitely fine threads discharged by the larvae of E. Thrax. The purpose of this study was to determine the type, quantity, and level of parasitism parasitoid of banana skipper at different altitude sites (lowlands and highland areas). In the highlands, two parasitoids were found namely Bracemeria lasus, and Cotesia erionotae. The percentage of Erionata Thrax was found highest in which of 60 Erionata Thrax samples observed four samples was attacked by Cotesia erionotae (6.667%) at the fourth month of observation. The lowest was Bracemeria lasus (1.176%) in which of 85 samples only one sample attacked at the first month observation.Â In the lowlands, the highest percentage was found in the second and fourth month observation where 3.333% of 60 samples was attacked by Cotesia erionotae parasitoids. While the lowest percentage of parasitoid attacks was found at the first month observation in which only one sample was attacked out of 85 samples (1.176%). These results shows that the percentage of parasitoids in the highlands has no significant effect on that of in the lowlands.Â Keywords: Banana, E.tharax, Parasitoids.